Wasathiyyah in Tafsir: A Semiotic Study of the Meaning of Moderation in the Qur'an - Sulaiman Ibrahim; Moh. Azwar Hairul (Pascasarjana IAIN Sultan Amai Gorontalo, 2024)
This study examines the meaning of moderation in the Quran using a semiotic approach, specifically through the interpretations of Hamka and Quraish Shihab on verses related to the concept of wasatiyyah. Wasatiyyah, which is interpreted as